Carbon dots-silver based fluorescence assay for the detection of Escherichia coli O157:H7 - Mohd Saad, Suria; Abdullah, Jaafar; Abdul Rashid, Suraya; Yap, Wing Fen; Salam, Faridah; Lau, Han Yih (Malaysian Society for Sensor Technology Development (SENSOR), 2023)
The detection of Escherichia coli O157:H7 (E. coli O157:H7) from various food matrices is important in the clinical field for the diagnosis of diseases. To identify the E. coli O157:H7 fliC gene; carbon dots (CDs), fluorophore-oligonucleotide, silver nanoparticles (AgNPs), quencher-oligonucleotide and target oligonucleotide were incorporated into the fabrication of single fluorescent sensor. The sensor works based on the principle of fluorescence quenching between CDs and AgNPs when the target oligonucleotide is co-hybridized with oligonucleotide on the surface of CDs (fluorophore) and AgNPs (quencher), respectively. AgNPs acts as a quencher by in situ absorption of CDs energy in the presence of target oligonucleotide. When the sensing system is excited at 340‰nm, the optimum emission at 450 nm, corresponding to CDs emission, appears and the interaction between CDs as fluorophore and AgNPs as quencher indicates the presence of fluorescence quenching. Fluorophore emission was triggered inversely proportional to the change in target concentration. The linear calibration plot towards target oligonucleotide was obtained in the dilution series from 0.001 nM to 200 nM with a detection limit (LOD) of 0.0088 ± 0.71 nM. The results of kinetic studies using fluorescence assay found a strong relationship and interaction between fluorophore and quencher.